Characterization of stewed beef by sensory evaluation and multiple intelligent sensory technologies combined with chemometrics methods. (15th May 2023) - Jiang, Shui; Zhu, Yiwen; Peng, Jinyue; Zhang, Yin; Zhang, Weiyi; Liu, Yuan
Abstract: Though stewed beef is favored by consumers, the impact of the domestic high-pressure stewing method on beef has received little attention. This study characterized the beef cooked under varied pressures in the household pressure cooker by analytical instruments, sensory evaluation, and multiple intelligent sensory technologies. Totally, 165 volatile compounds were identified by SPME-GC-TOF-MS, with more detected in samples with higher pressure. The glutamic acid contributed significantly to the umami taste of beef (TAV > 1.25). The meaty and fatty odor, hardness, chewiness, and sweet taste contributed to the overall liking of stewed beef ( P < 0.05). The multiple-target BPNN model based on fused data from multiple intelligent sensory technologies could simultaneously predict sensory perception intensities with a satisfying performance ( R 2 > 0.9340), but could not efficiently predict subjective overall liking scores. The study guides the domestic cooking of beef stew and quantitative sensory prediction based on multiple intelligent sensory techniques.